Sinkhole attack detection based on fusion of ACO and P2P trust model in WSN - Wumaier HENIGULI (Dianxin kexue)
For the Sinkhole attack problem of wireless sensor network（WSN），a detection algorithm based on fusion of ant colony optimization（ACO）and P2P trust model was proposed.Firstly，ant colony optimization algorithm was used to detect the existence of a Sinkhole attack in route and generate the alarm information of sensor nodes. Then，Boolean expression evolve sign generation algorithm was used to distributed keys for group alarm nodes，and it was used to mark suspicious nodes. Finally，P2P trust model was used to compute trust value of each suspicious node，and the node with trust value was lower than the preset threshold as invasion of node. The analysis shows that the proposed algorithm need less matching search times in matching process than binary search algorithm and the rules matching based neural network（RMNN）algorithm，which indicates that it has improved the efficiency of the algorithm. Experimental results show that the proposed algorithm has higher detection accuracy on Sinkhole attack than RMNN algorithm.